Multimedia instruction of cardiac auscultation. - Criley, J. M. (American Clinical and Climatological Association, 1997)
The cardiac physical examination is in itself a multimedia experience. It is an amalgamation of visible, palpable, and audible sensations, preceded by the collection of an appropriate historical context in which to place these multiple sensations. It is unlikely that any electronic media could ever replace the real life experience of admitting, examining, diagnosing, and effectively treating a patient with mitral stenosis who has decompensated because of the onset of atrial fibrillation with rapid ventricular response, or a patient with sudden, severe aortic regurgitation due to endocarditis. These potentially fatal conditions can be effectively treated only if the suspicion of their presence is seriously raised. Although there is no substitute for first-hand experience, attempts to provide an effective surrogate experience are worth pursuing.